(3GdLhGgQ GdSfjI aj TQM GdCLQhejIs - (3CHheMeO YHO Gddg (B((3GdeOYh HYHjO(B) (3Hf CHj GdaVd (B((3Hf CHj GdbGSe(B) (3Hf eMeO Hf YHjOGddg GdaGSj GdKYGdHjs; (3GHf GLQhe , CHh YHO Gddg eMeO Hf eMeO Hf OGhO GdUfgGLj,J (B723 (3g` s ((3GdYQHj Hf CMeO Hf eMeO Hf YHOGdeDef GdOGhOj GdTQja s)
(3ChdgG (B:s
(3hHYO, adeG hVY GdTjN GHf BLQhe GdebOeI GdLQhejI GYJfi HgG cKjQ ef GdfGS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdBLQhejI ebOeI ai GdfMhs
(3HBNQgG WeS TOjOs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs